Analisis Kesalahan Berbahasa pada Artikel Lingkungan dalam Website Nationalgeographic.co.id Edisi Januari 2025 sebagai Sumber Bacaan dan Informasi - Putri Lestari; Hana Zaita Alhuwaida; Syahrul Ramadhan; Izza Afkarina Fauziyyah; Alisya Pramesti; Asep Purwo Yudi Utomo; Muhamad Haryanto; Eko Ahmad Riyanto (BADAN PENERBIT STIEPARI PRESS, 2025)
Human communication aims to convey specific goals and objectives from the speaker to the listener, where the language used has an important role in building a communicative situation. Language skills include reading, speaking, writing, and listening. One of writing skills is article writing. However, in writing online articles, language errors are still a common occurrence and a daily phenomenon. The purpose of this study is to analyze language errors contained in environmental-themed articles on the nationalgeographic.co.id website in the January 2025 edition. This research focuses on three linguistic errors, including the first, the selection of diction; the second, the wrong use of conjunctions; and the third, the wrong use of punctuation. The method used in this research is a descriptive qualitative approach, which relies on data collection techniques. The data collection techniques used include listening and taking notes. The results showed that there were several language errors in the articles, including the use of non-standard diction, errors in conjunction selection, and improper use of punctuation. This can affect the quality of information provided to the public because it has the potential to cause reader misinterpretation. This research is expected to contribute to raising awareness about the importance of using good and correct language, especially in writing scientific works such as articles that become sources of information. In addition, this research also aims to provide a deeper understanding of the language errors that are often encountered in online articles and ways to correct them so that the information conveyed becomes more effective.